A Comparison of the Effect of Cognitive Specific and General Imagery on Skills Performance of 7-10-Year-Old Soccer Players - Mehrzad Kharestani; Mojtaba Esmaeeli Abdar; Ahmad Ghotbi Varzaneh (University of Tehran, 2015)
The aim of the present study was to examine the effect of different types of imagery on the skills performance of 7-10-year-old soccer players. 45 children (mean age 8.44±1.13 year) with similar imagery abilitywere selected and randomly assigned to three groups (each group 15 subjects). The training protocol was performed three sessions a week for 6 weeks. Data analysis indicated a significant difference between the groups in acquisition (P=0.001) and retention (P=0.002) phases. The results of Tukey post hoc test in the acquisition phase indicated no significant differences between cognitive specific imagery group and cognitive general imagery group (P=0.53) but there were significant differences between cognitive specific imagery group and traditional imagery group (P=0.006) and also between cognitive general imagery group and traditional imagery group (P=0.03). Also, in the retention phase, the results of Tukey post hoc test indicated significant differences between cognitive specific mental imagery group and traditional mental imagery group (P=0.002), between cognitive specific mental imagery group and cognitive general mental imagery group (P=0.037) and between cognitive general imagery group and traditional imagery group (P=0.001). With regard to the findings, the role of the cognitive specific imagery was in the center of attention more than before and soccer instructors and coaches are recommended to use this type of imagery.